2010
DOI: 10.19030/ajbe.v3i12.966
|View full text |Cite
|
Sign up to set email alerts
|

Learning Effectiveness Using Different Teaching Modalities

Abstract: <p class="MsoNormal" style="text-align: justify; line-height: normal; margin: 0in 0.5in 0pt; mso-pagination: none;"><span style="font-family: &quot;Times New Roman&quot;,&quot;serif&quot;; font-size: 10pt;">There is much discussion about whether online instruction is as effective as face-to-face instruction.<span style="mso-spacerun: yes;">&nbsp; </span>To address this question, a comparative study was made of two sections of an MBA <span style="mso-spacerun: yes;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
14
0
4
Order By: Relevance
“…The exam held for both groups showed that the online group was more effi cient, according to both the exam results and the students' own perceptions [2].…”
Section: Problem Description and Literature Reviewmentioning
confidence: 95%
“…The exam held for both groups showed that the online group was more effi cient, according to both the exam results and the students' own perceptions [2].…”
Section: Problem Description and Literature Reviewmentioning
confidence: 95%
“…A variável critério Aprendizagem foi avaliada segundo o desempenho obtido pelos alunos nas avaliações presenciais parciais e finais propostas durante as disciplinas analisadas, sendo medida em termos da média das notas adquiridas. O fenômeno em questão pode não ser adequadamente alcançado através do desempenho acadêmico, sendo importante relativizar a medida de aprendizagem, que é frágil e pouco complexa, mas as notas ainda são o mecanismo mais usual e comumente utilizado em instituições de ensino para medir a aprendizagem dos estudantes e, consequentemente, nas pesquisas sobre o tema, como estudos comparativos sobre EAD e como preditoras de sucesso acadêmico (Borges-Ferreira, 2005;Carrol & Burke, 2010;Ramos & Yudko, 2008).…”
Section: Modelo De Investigação E Variáveis De Interesseunclassified
“…Un primer conjunto de investigaciones no encontró diferencias estadísticamente significativas entre los logros evidenciados por grupos de estudiantes de cursos virtuales y tradicionales sobre el mismo contenido (Coma, 2006;Kirtman, 2009;Carrol & Burke, 2010;Gibson, 2008;Brownstein & Gerlowski, 2008;Larson & Sung, 2009;Tutty & Kleine, 2008), casi independientemente del área y de la medida de logro utilizada en dichos estudios.…”
Section: Introductionunclassified